Gospoda-tovarishchi . Gospoda-tovarishchi . Gentlemen-Comrades . Господа-товарищи - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The program considers debates around legitimacy (or lack thereof) of some deputies' presence in the State Duma. Featured in the program: IAvlinskii, Grigorii Alekseevich (Deputy of the State Duma) Contributors: Omel'ianiuk, Ol'ga (Anchor) Передача о спорах вокруг легитимности присутствия некоторых депутатов в Государственной думе. В программе участвуют: Явлинский, Григорий Алексеевич (Депутат Государственной Думы) Создатели: Омельянюк, Ольга (Ведущий/Ведущая)